528 REM Sleep Without Atonia in Idiopathic REM Sleep Behavior Disorder in the North American Prodromal Synucleinopathy Cohort. (3rd May 2021) - Feemster, John; Timm, Paul; Teigen, Luke; Faber, Sarah; Steele, Tyler; McCarter, Stuart; Boeve, Bradley; Hedtkamp, Kristina; Ju, Yo-El; McCleland, Jennifer; Postuma, Ronald; Pelletier, Amelie; et al.
Abstract: Introduction: Idiopathic/isolated REM sleep behavior disorder (iRBD) is a prodromal alpha-synucleinopathy characterized by dream enactment behavior and REM sleep without atonia (RSWA). We sought to define quantitative RSWA diagnostic thresholds in the North American Prodromal Synucleinopathy (NAPS) Consortium cohort. We analyzed RSWA between iRBD patients across participating NAPS sleep centers, compared to normative controls, and hypothesized that previous diagnostic RSWA thresholds were overestimates. Methods: All digital polysomnography files were converted to European Data Format and scored at a central laboratory (Mayo Clinic) which standardized display scoring montages, channel sensitivities, and filtering, and scripted computational analyses for visual scoring. RSWA was quantitatively analyzed in the submentalis (SM) and anterior tibialis (AT) muscles in iRBD (n=86) patients and controls (n=118) utilizing well validated visual (Mayo) and automated (RAI) methods. Parametric statistics were used to compare RSWA metrics, and RSWA thresholds were developed using receiver operating characteristic curves. Results: RSWA was significantly higher for the RAI and all visual individual and combined muscle activity metrics in iRBD compared to controls (all p<0.001). Average SM phasic measures were: 14.2% (Mayo), 17.9% (McGill), 18.5% (UCLA), and 9.4% (Washington University). Average AT phasic measures at each site were: 26.7% (Mayo), 17.1% (McGill), 23.3% (UCLA), and 17.4% (Washington University). Average SM/AT 'any' measures at each site were: 45.4% (Mayo), 35.9% (McGill), 53.4% (UCLA), and 23.5% (Washington University). Overall cohort RBD diagnostic thresholds (AUC, specificity/sensitivity) were: SM phasic 4.9% (90.0, 82.2%/83.7%); AT phasic 7.6% (88.7%, 82.2%/81.4%) and combined SM/AT 'any' 13% (94.6, 83.9%/96.5%). Conclusion: RSWA thresholds in the NAPS cohort were substantially lower than previously reported, suggesting previously overestimated diagnostic RSWA thresholds due to smaller, enriched patient samples and overfit statistical modeling. Confirmation of these findings in the complete NAPS cohort (n=300 iRBD patients across all 10 NAPS centers) is planned. Support (if any):